2011
DOI: 10.1002/jor.22016
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and differentiation of human tenocytes in response to platelet rich plasma: An in vitro and in vivo study

Abstract: Platelet rich plasma (PRP) is the autologous plasma fraction with a platelet-rich cellular component which is enriched with a number of growth factors. Due to its availability and low cost, PRP has become an increasingly popular clinical tool as an alternative source of growth factors for various applications, for example, tendon regeneration but with limited success in clinical trials. The main objective of the current study was to determine whether activated PRP [i.e., platelet rich plasma-clot release (PRCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 47 publications
(74 reference statements)
4
64
0
2
Order By: Relevance
“…Alfa granules of platelets contain a wide range of growth factors, including PDGF, TGF-β, PDAF, VEGF, EGF, PDEGF, ECGF and IGF. 9 It has been reported that the use of platelets is beneficial for healing of bone, 10 cartilage, 11 tendon, 12 hernia 13 and skin 14 defects. One of the main advantages of using platelets as a source of growth factor is the possibility of autologous use, which reduces the immune reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Alfa granules of platelets contain a wide range of growth factors, including PDGF, TGF-β, PDAF, VEGF, EGF, PDEGF, ECGF and IGF. 9 It has been reported that the use of platelets is beneficial for healing of bone, 10 cartilage, 11 tendon, 12 hernia 13 and skin 14 defects. One of the main advantages of using platelets as a source of growth factor is the possibility of autologous use, which reduces the immune reaction.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the effect of PRP on human tendon cells, controlled clinical trials are important, but detailed in vitro studies are also critical. In most of the studies that have been performed, the concentration of PRP was expressed as a percentage, making it impossible to understand how many platelets/ μ L were effectively used [17, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…data]; hence, these two growth factors were excluded in this selection procedure. Our previous research has also indicated that platelet-rich plasma has a very potent effect in promoting tenocyte expansion and differentiation: high-level research trials have yet to prove its efficacy [Wang et al, 2011].…”
Section: Introductionmentioning
confidence: 99%